Crystal quartz backed tools from the Howiesons Poort at Sibudu Cave - (:unkn) unknown (My University, 2006)
A technological analysis of crystal quartz backed tools from the Howiesons Poort of Sibudu Cave shows that they are smaller than backed tools from other rock types. They are not highly standardized and their reduction sequence is straightforward. Raw materials could have been obtained near the shelter. The distribution of organic and inorganic residues on the backed tools suggests that they were hafted. Our results imply that interpretations of Howiesons Poort technology as innovative, based on attributes such as long distance transport of raw materials and size standardization of backed pieces, remain undemonstrated.
Keywords: African Research